Disparities in health and access to healthcare between asylum seekers and residents in Germany: a population-based cross-sectional feasibility study - Tunkl, Christine; Joos, Stefanie; Bozorgmehr, Kayvan (BMJ open, 2015)
Objectives To assess disparities in health and healthcare between asylum seekers (AS) and residents in Germany as a proof of concept using European Core Health Indicators (ECHI). - Design Population-based cross-sectional feasibility study. - Participants All AS (aged 18 years or above) registered in three counties in Germany during a 3-month study period (N=1017). Cross-sectional data on the resident population were taken from the German Health Interview (2008-2011, N=8152), and the European Union Statistics on Income and Living Conditions (2012, N=23 065). - Outcome measures Self-reported health status and healthcare access (utilisation and unmet medical need) in line with ECHI. - Method Inequalities in health and access to healthcare were quantified both by crude and age-stratified/sex-stratified ORs with 95% CI using cross-tabulations. - Results A total of N=156 AS (15.34%) participated in the study. Compared with residents, AS were significantly more likely to report a bad health status (OR=1.72 (1.23 to 2.41)), activity limitations (OR=1.97 (1.39 to 2.79)) or (only younger age groups) any chronic morbidity (18-24 years: OR=6.23 (2.62 to 14.57); 25-49 years: OR=2.05 (1.23 to 3.37)). AS had significantly lower odds for consulting any physician (OR=0.1 (0.07 to 0.16)) or general practitioners (OR=0.44 (0.31 to 0.62)), but higher odds for hospital admissions (OR=2.29 (1.54 to 3.34)), visits to psychotherapists (OR=4.07 (2.48 to 6.43)) and unmet needs (OR=3.74 (2.62 to 5.21)). The direction of healthcare-related associations was consistent across all strata despite variation in magnitude and statistical significance. - Conclusions Quantifying disparities between AS and the resident population by means of selected ECHI proved to be feasible. The approach yielded first quantitative evidence for disparities in health and access to healthcare in the German context. Further research is needed to generate representative estimates, for example, by including AS in national health monitoring programmes.
Gesehen am 07.07.2020